Emotional intelligence 2.0 ebook - Greaves, Jean (2009)
FOREWORD BY PATRICK LENCIONI, BESTSELLING AUTHOR OF THE FIVE DYSFUNCTIONS OF A TEAM. Emotional Intelligence 2.0 is a book with a single purpose—increasing your EQ. Here's what people are saying about it: Emotional Intelligence 2.0 succinctly explains how to deal with emotions creatively and employ our intelligence in a beneficial way." —THE DALAI LAMA A fast read with compelling anecdotes and good context in which to understand and improve." —NEWSWEEK Gives abundant, practical findings and insights with emphasis on how to develop EQ." —STEPHEN R. COVEY This book can drastically change the way you think about success...read it twice." —PATRICK LENCIONI In today's fast-paced world of competitive workplaces and turbulent economic conditions, each of us is searching for effective tools that can help us to manage, adapt, and strike out ahead of the pack. By now, emotional intelligence (EQ) needs little introduction—it's no secret that EQ is critical to your success. But knowing what EQ is and knowing how to use it to improve your life are two very different things. Emotional Intelligence 2.0 delivers a step-by-step program for increasing your EQ via four, core EQ skills that enable you to achieve your fullest potential: 1) Self-Awareness 2) Self-Management 3) Social Awareness 4) Relationship Management